Comparison Analysis Of Camels And Rgec In Assessing The Level Of Health Of Bank (Case Study In Pt Bank Rakyat Indonesia (Persero), Tbk Period 2017-2019) - Dwitama, Faramita (Publisher Cv. Inara, 2021)
Bank soundness is the ability of a bank to carry out normal banking operations and is able to fulfill all of its obligations properly in ways that are in accordance with applicable regulations.This study aims to determine the comparison of the soundness level of the bank using the CAMELS method and the RGEC method at PT Bank Rakyat Indonesia (Persero), Tbk for the period 2017-2019. The type of data used is quantitative data and the data source used is secondary data.The results of this study indicate that (1) the soundness level of the bank at PT Bank Rakyat Indonesia (Persero), Tbk for the 2017-2019 period using the CAMELS method in the predicate